Affiliation and classroom interaction management: implications of this relationship for teacher training - Perobelli, Roberto; Goulart, Ana Carolina Fracalossi; Coan, Ana Luiza Henriques (The ESPecialist, 2025)
When the context of big changes in the education field and the actions developed by teachers inside the classroom take place, it is urgent that Applied Linguistics focuses on the studies with a look into the affective relation between teachers and students. This article aims to investigate, in a qualitative way, the relation between the concept of affiliation (Lindström; Sorjonen, 2013) - arising from the Conversation Analysis area - and the classroom for the teacher training. In this paper, we will analyze data from a 6th grade class in the elementary school, in a context of a religious education lesson, where the students were invited to discuss a common topic present in their reality, the femicide (Goulart, 2020; Coan, 2022). We aim in this paper to highlight how different interactional resources which indicate affiliation practices, can be identified and used in the teacher’s practice in the classroom, providing opportunities for knowledge construction processes. The results show that affiliation, in classroom interactions, involves agreement, empathy or solidarity, and how the teacher’s sensitive view of this interactional resource encourages an active and safe participation by students, providing a relevant space for the expression of different opinions, which generates, as an effect, mutual respect. Furthermore, it is worth to emphasize that multimodality (Mondada, 2016) allows us to analyze, beyond the verbal interaction, the embodied actions and then, it is possible to affirm that the verbal and corporal affiliation practice tends to reinforce students’ confidence and self-esteem, encouraging them to participate more actively in discussions and to express their opinions in an open and safe manner.